Response of transient soil waterlogging on shoot growth pattern and root architecture of finger millet and barnyard millet seedlings - Sherpa, D; Kumar, S; Mishra, S (Plant Science Today, 2024)
Millets, as key crops in semi-arid and arid tropical regions, are gaining recognition for their nutritional benefits and resilience to challenging conditions. Finger millet and barnyard millet, in particular, stand out for their nutrient profiles and adaptability. However, research on their response to waterlogging, a major abiotic stress, remains limited. This study aimed to examine the immediate response of finger millet and barnyard millet seedlings to transient waterlogging conditions, focusing on their growth patterns and changes in root architecture to understand their morpho-physiological adaptive strategy. Seedlings were subjected to varying durations of waterlogging: control, 48, 74, and 120 hours to assess parameters such as shoot and root characteristics, leaf growth, and tolerance indices. Results showed a decrease in root length and an increase in shoot length with prolonged waterlogging. Root and shoot biomass, along with seedling dry weight, rose as waterlogging durations increased. Significant increases were observed in root surface area, volume, and the number of root tips and forks. Leaf area initially expanded but declined after 72 hours of waterlogging, accompanied by changes in specific leaf area and chlorophyll concentration. Tolerance indices, such as root-to-shoot ratio, decreased under waterlogging conditions, with finger millet exhibiting higher tolerance than barnyard millet. These findings provide insights into the adaptive strategies of millets under waterlogging, which is valuable for crop management and breeding for enhanced stress tolerance.